(untitled) (European Journal of Mental Health, 2015)
Binding and Loosing in the Course of a Career: The Three Important Psychological Stages of Development in and of the Family: At certain stages of everyone’s career the family constitutes the most important milieu of physical, psychological and social development. However, it is important for family members to change not only as individuals but together as a family in order to ensure that they can mutually help, strengthen and support each other in certain situations and at certain stages of life. For that, families and individual family members need internal and external resources, social confidence and participation on the one hand, and capability for emotional resonance on the other. When a family is established, at the birth of the first child, during the transition period when children reach young adulthood until they leave home, and, finally, at the time when elderly children provide care for their very old parents, valuable family resources and the necessary family competencies become particularly visible.